Uji Coba Rangka Tenda PKL Wahidin dengan Pendekatan Community Development - Imelda Irmawati Damanik; Yohanes Satyayoga Raniasta; Tutun Seliari (Journal of Innovation and Community Engagement, 2022)
Street Vendor Tents (Pedagang Kaki Lima in Bahasa Indonesia, PKL) are an important element of informal economy activities, because it is one of the vacancies that can be found in various corners of the urban area, such as Dr. Wahidin Sudirohusodo street. Therefore, design for street venders’ tent is become important, because it will influence the image of the area with very active vibrant activities.. Designing street vendor’s tent is not an easy matter, because it is related to the government’s policies and also related to the technical structure. The study is co-working with PPKLY and APKLY. This partnership used community development approach, carried out by focus group discussion (FGD) because basically the street vendors understand their needs. The companion will provide an affordable design and lead the design to keep it in line with government policy. We hope the frame’s trial will develop a sustainable design which it is suitable for the PKL needs and also able to strengthen the image of the city area. Thus, the informal economic activities of street vendors can go hand in hand with the government's policies and meet the requirements of cleanliness, safety and have an aesthetic that strengthens the image of the area. And of course, this frame’s assembly must be easily understood by street vendors, because they are the ones who will use it.